Du labyrinthe des rues au labyrinthe de l'etre - Brunel, Pierre (Amaltea. Revista de Mitocrítica, 2009)
There are other labyrinths apart from Crete’s: the streets of a big city like Paris for Gérard de Nerval, or London for T.S. Eliot. Even more complex is the labyrinth of the human being where those who Pierre Seghers called in his 1972 anthology (reviewed and completed in 1978 and 1985) « les nouveaux poètes maudits » (« the new accursed poets ») wondered or got lost. Three of them will be studied in this article: Jacques Prével (1915-1951), Jean-Pierre Duprey (1930-1959) and specially Roger-Arnould Rivière (1930-1959), an admirable unknown poet who believed having recognized Dylan Thomas’ « intricate image » in his first poems and who wrote restlessly and beautifully his « vertigineux à-pic de la nuit ».